A Facile and Mild Approach for Stereoselective Synthesis of α-Fluoro-α,β-unsaturated Esters from α-Fluoro-β-keto Esters via Deacylation - Qian, Jinlong; Yi, Wenbin; Lv, Meifang; Cai, Chun (Synlett, 2015)
The highly stereoselective olefination reaction of α-fluoro-β-keto esters for the synthesis of α-fluoro-α,β-unsaturated esters has been developed. The olefination combines nucleophilic addition, intramolecular nucleophilic addition, and elimination in one step, as well as provides a facile synthetic approach to α-fluoro-α,β-unsaturated esters which are important units in many biologically active compounds and useful precursors in a variety of functional-group transformations.
Keywords: olefination; highly stereoselective; deacylation; fluoroolefins; carbon–carbon bond cleavage